Rineloricaria quilombola: a new species of whiptail catfish (Siluriformes, Loricariidae, Loricariinae) from upper and middle Tocantins River basin, Brazil - Chamon, Carine C.; Fichberg, Ilana (Zootaxa, 2022)
The genus Rineloricaria comprises 69 valid species and has been considered monophyletic by some authors. The taxonomic history of Rineloricaria is quite complex, especially concerning its wide distribution and morphological plasticity that make it difficult to diagnose and describe new species. Even with the great species-richness of the genus and the huge diversity of the system, the Tocantins-Araguaia River basin hosts only three formally described species of Rineloricaria: R. hasemani, R. lanceolata, and R. osvaldoi, the former is known from lower Tocantins River, R. lanceolata widespread along Amazon basin and the last one restricts to the Araguaia River basin. Recent field expeditions and collection examination revealed an undescribed species of the genus from the upper and middle Tocantins River drainage. The new species is diagnosed among its congeners by having a greater number of premaxillary and dentary teeth (both with up to 15 vs. up to 10 in most congeners). From R. hasemani it is also distinguished by having the edge of snout straight in lateral view and absence of filaments on lower lip. It is also diagnosed from R. lanceolata by having wider cleithral width and a quite different color pattern, lacking a hyalin spot on the base of pectoral and pelvic fins; and from R. osvaldoi by having a lower head depth, triangular head in dorsal view, shorter snout length and other features.